Tafsir Konsep Futuwwah: Kebajikan yang Mengagumkan - Media Zainul Bahri (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2005)
In the Qur’an, the term “futuwwah” refers to “an ideal, noble, and perfect person, one whose hospitality and generosity are endless until they have nothing left for themselves, someone who selflessly gives everything they own, including their own life, for the sake of their companions.” In the perspective of Sufi mystics, futuwwah signifies heroic generosity, praiseworthy conduct following the example of the prophets, saints, sages, companions, and lovers of God. This ideal is perfectly exemplified by Prophet Muhammad (peace be upon him). Several examples of the tradition of generosity are seen in the character of Prophet Ibrahim, who obediently followed Allah’s command to sacrifice his son for the sake of Allah.